A Structural Design of COVID-19 Patient Lifting Device Using Crane and Hydraulic Mechanism - Dindamilenia Choirunnisa Hardiyasanti; Sinta Widianingrum; Fini Bestiara; Mei Syaroh; Farid Triawan (Journal of Mechanical Design and Testing, 2021)
COVID-19 has brought the mankind into the worst condition. The health care workers as the forefront player during this pandemic are psychology and physically exhausted. In 2021, the infected patient is decreasing in some countries, yet increasing in others. Therefore, this study is aimed to design and analyze a patient lifting device in order to help the health workers in handling paralyzed and bone traumatic patients in effective way. This lifting device is designed to be operated by only one person and contactless with the patient. Thus, the healthcare worker can work on safety procedure of COVID-19. The structural design of the device is using the concept of crane and hydraulic mechanism that can handle a maximum weight of 2,000 N. Every mechanical part that is considered critical becomes the focus in the strength analysis. The analysis is done by theoretical approach under static and dynamic loading. As the results, the static and fatigue analyses show that the most critical part of the lifting device is at the fork structure with safety factor of 1.04. This indicates the design is in safety condition and could have an infinite service life cycle.